2004
DOI: 10.1128/ec.3.1.232-240.2004
|View full text |Cite
|
Sign up to set email alerts
|

A WD40 Repeat Protein Regulates Fungal Cell Differentiation and Can Be Replaced Functionally by the Mammalian Homologue Striatin

Abstract: Fruiting body development in fungi is a complex cellular differentiation process that is controlled by more than 100 developmental genes. Mutants of the filamentous fungus Sordaria macrospora showing defects in fruiting body formation are pertinent sources for the identification of components of this multicellular differentiation process. Here we show that the sterile mutant pro11 carries a defect in the pro11 gene encoding a multimodular WD40 repeat protein. Complementation analysis indicates that the wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
167
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(173 citation statements)
references
References 49 publications
(60 reference statements)
6
167
0
Order By: Relevance
“…The phenotype of the ⌬SmtA-2 and ⌬SmtA-2/3 strains is similar to that of sterile S. macrospora pro mutants blocked at the stage of protoperithecium formation and mutant ⌬Smta-1, which have been described previously (47,52,55,64,65). Complementation analysis of ⌬SmtA-2 and ⌬SmtA-2/3 was performed by transformation with a plasmid carrying a genomic fragment comprising the SmtA-2 or SmtA-3 gene under the control of its own 5Ј and 3Ј regulatory elements, resulting in strain ⌬SmtA-2:SmtA-2 ect , ⌬SmtA-2/3:SmtA-2 ect , or ⌬SmtA-2/3:SmtA-3 ect carrying SmtA-2 or SmtA-3 integrated ectopically under the control of the native promoter.…”
Section: Resultssupporting
confidence: 72%
“…The phenotype of the ⌬SmtA-2 and ⌬SmtA-2/3 strains is similar to that of sterile S. macrospora pro mutants blocked at the stage of protoperithecium formation and mutant ⌬Smta-1, which have been described previously (47,52,55,64,65). Complementation analysis of ⌬SmtA-2 and ⌬SmtA-2/3 was performed by transformation with a plasmid carrying a genomic fragment comprising the SmtA-2 or SmtA-3 gene under the control of its own 5Ј and 3Ј regulatory elements, resulting in strain ⌬SmtA-2:SmtA-2 ect , ⌬SmtA-2/3:SmtA-2 ect , or ⌬SmtA-2/3:SmtA-3 ect carrying SmtA-2 or SmtA-3 integrated ectopically under the control of the native promoter.…”
Section: Resultssupporting
confidence: 72%
“…Inspection of Dmak-2 grown on cornmeal agar plates for 10 days revealed no mature and fertilization-competent protoperithecia (female sexual structures in N. crassa), but did reveal an $50-fold reduced number of protoperithecia-like structures in comparison to wild type ( Figure 3A). Furthermore, the protoperithecia-like structures produced in the Dmak-2 strain were smaller, less developed, and nonfertile, but morphologically resembled immature protoperithecia of wild type (e.g., Poggeler and Kuck 2004;Poggeler et al 2006). This indicated that loss of the MAK2 pathway function does not abolish the capability of initiating protoperithecia formation, but rather affects their abundance and, more importantly, their maturation into fertile structures.…”
Section: Resultsmentioning
confidence: 92%
“…This is best documented in mutants characterized in N. crassa (Wilson and Dempsey 1999;Perkins et al 2001;Xiang et al 2002;Fleissner et al 2005) and the closely related fungus Sordaria macrospora (Poggeler and Kuck 2004;Engh et al 2007), but was also observed in A. nidulans (Wei et al 2003). The hypothesis that hyphal fusion is functionally linked with sexual fruiting-body formation is also supported by our characterization of the suppression of the mak-2 pathway by cot-1(ts): the lack or delay of hyphal fusion correlated with defects in the formation of protoperithecia.…”
Section: Discussionmentioning
confidence: 96%
“…So far, several environmental and endogenous signals have been described to regulate fruiting body-dependent gene expression in a temporal and spatial manner (for a review, see reference 55). However, even though a decent number of genes involved in this process have been identified, the molecular determinants of fruiting body development have yet to emerge.In this study, we have investigated the homothallic ascomycete Sordaria macrospora, which was recently developed as a model system to study fruiting body morphogenesis (27,36,37,43,52). During early sexual propagation, S. macrospora forms female gametangia, so-called ascogonia, on vegetative hyphae.…”
mentioning
confidence: 99%